2016
DOI: 10.1080/13647830.2016.1242156
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of incipient carbonaceous nanoparticle formation at flame conditions

Abstract: Particle nucleation remains one of the most intriguing steps in the process of particle formation in flames. Although stacking/clustering of polycyclic aromatic hydrocarbons (PAHs) has been identified as a key step in the nucleation process, uncertainties remain about the size of the PAHs undergoing clustering, the organisation of the PAHs in the forming clusters and the factors affecting the relative amounts of order and disorder present in the texture organisation. A molecular dynamics approach is presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Similar conclusions were reached by a recent molecular dynamic study, showing that pyrene dimerization at 1500 K is almost impossible [237]. It was further estimated that a 3.6 bar partial pressure of pyrene is required for 1% pyrene to be converted to dimers at 1500 K, while in practical hydrocarbon flames, the volume fractions of pyrene are generally on the order of 10 -6 .…”
Section: Soot Nucleationsupporting
confidence: 79%
“…Similar conclusions were reached by a recent molecular dynamic study, showing that pyrene dimerization at 1500 K is almost impossible [237]. It was further estimated that a 3.6 bar partial pressure of pyrene is required for 1% pyrene to be converted to dimers at 1500 K, while in practical hydrocarbon flames, the volume fractions of pyrene are generally on the order of 10 -6 .…”
Section: Soot Nucleationsupporting
confidence: 79%
“…Molecular dynamics uses classical mechanics to study the movement and behaviour of molecular systems over time and provides valuable information about molecular interactions and ar-rangements of nascent soot particles (Totton et al, 2012;Chen et al, 2014b,a;Iavarone et al, 2016;Grancic et al, 2016;Chung and Violi, 2011;Elvati and Violi, 2013;Bowal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…All the above mechanisms are believed to take part in the soot formation process, but their relative importance or feasibility at different conditions and temperatures is still unclear. Previous studies utilising different atomic simulation methods, such as density functional theory (Zhang et al, 2014), molecular dynamics (MD) (Schuetz and Frenklach, 2002;Totton et al, 2012Totton et al, , 2010Chung and Violi, 2011;Iavarone et al, 2017;Pascazio et al, 2017;Mao et al, 2017Mao et al, , 2018, Monte Carlo (Rapacioli et al, 2005) and well-tempered metadynamics simulations Violi, 2018, 2013) have shown that the physical interactions between medium-sized PAH are not strong enough to stabilise clusters at high temperatures, and only aromatic molecules as big as circumcoronene are able to cluster at temperatures where soot forms (≈1500 K). Understanding the degree of crosslinking in soot particles could then be important for determining which mechanisms are involved in their growth and potentially help in understanding their inception process.…”
Section: Introductionmentioning
confidence: 99%